A Comparative Study of University Library Websites of Nepal - Manandhar, Nira (Access: An International Journal of Nepal Library Association, 2023)
Universities bear the responsibility of delivering higher education and research work. To achieve this goal, well-facilitated libraries are required. In the present scenario, the daily work of people is becoming easier with the use of internet. Hence, libraries and their services also need to show their presence on the web. The websites of Universities of Nepal have been explored using a checklist prepared for the purpose, of finding the status of central library websites and their services available via websites. The result showed that there is no uniformity in managing information in websites and available IT facilities are not being used properly in such an important sector of education. Library professionals now should make an effort to maintain uniformity in library websites which is now as much essential as the uniformity of cataloguing and classification work of libraries.